Pelatihan Seni Baca Al-Qur’an Dalam Meningkatkan Kualitas Tilawah Di Lembaga TPQ Al-Huda Desa Kebonrejo Kediri - Dhea Nur Izzah; Siti Nurul Ifadah (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2022)
The Qur'an is the kalam of Allah which is mu'jiz, which was passed down to the Prophet Muhammad SAW. The Qur'an for Muslims has a very important role in daily life. Therefore, Qur'anic education must be instilled from an early age by reading, living, and understanding it, then applying it to daily activities, so that a distinctive life is realized. In the study itself, the author chose to use the PAR (Participatory Action Research) method. The results of this study, performed several steps as follows; The first step we take is to prepare the material that we will deliver. The second step is to carry out a learning plan or rather called the learning process. The third step is to evaluate the tilawah learning that has been carried out from beginning to end to the children. This is an attempt to find out the extent of the learning that has been captured by children during learning.